Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan Sustainability Reporting - Ihsan Syakirli; Charoline Cheisviyanny; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2019)
This research aims to give empirical evidences about company’s characteristics effects on sustainability reporting disclosure. Information in company’s sustainability report disclosure was collected by using GRI indicators. This research is an associative causal. All of company that listed on BEI for 4 years start from 2013 through 2016 used as population in this research while sample was defined bu purposive sampling method and 11 companies as sample. Type of data that we used was secondary data (panel data) from www.idx.com and company’s website. Data collection method used documentation method and multiple regression analysist method. The result are profitability, company’s size and industrial type have no effect on company’s sustainability reporting disclosure. The result of this study contribute directly to the knowledge of corporations providing voluntary disclosure information in form of quality sustainability reports and the importance of the development of globally accepted sustainability reporting standards.